ECONOMICS OF THE COMMON MIXTURE OF MIXED CROPPING IN THE SEMI-ARID TRACT OF CENTRAL RAJASTHAN - Jain, K C; Bajpai, M R (Annals of Arid Zone, 2016)
An experiment was conducted at the College of Agriculture Farm, Jobner to compare the economics of cultivation and net profit received through various crop mixtures (1/2 : 1/2)) in kharif, 1969. The results are summarised as follows. Among the various crop mixtures maximum net profit was recorded with the mixture bajra + guar. In different mixtures of til + legumes the maximum profit was recorded with til + guar followed by til + cowpea. Bajra alone produced a net profit of Rs. 1J67/ha which was Rs, 330/ha more than til alone. This profit could be compared with the mixtures of bajra +-moth and bajra + moong, but not with bajra + cowpea (net profit Rs. 737ha only). For taking higher net profit through mixed cropping guar should be prefered among the associated crops (legumes) and bajra among the main crops. Bajra + guar was the best crop mi"ture for getting the maximum net profit. Bajra + moong should be prefered over bajra alone as the profits are comparable but the soil fertility could better be maintained in bajra legume mixture than bajra alone.